Hip hemiarthroplasty with modular neck: is it useful in residents' learning curve? A prospective clinical trial. Issue 2 (December 2020) - Solarino, Giuseppe; Moretti, Lorenzo; Vicenti, Giovanni; Bizzoca, Davide; Piazzolla, Andrea; Moretti, Biagio
Background: The number of femoral neck fractures (FNFs) worldwide will drastically increase in the next few decades, reaching 6.3 million by 2050. In the future, therefore, newly-qualified orthopaedic surgeons will treat this kind of injury more frequently than in past decades. This prospective observational study aims to assess whether hip hemiarthroplasty with modular neck, performed via the Hardinge approach, can be safely carried out by orthopaedic residents. Methods: Patients referred to our Level I trauma centre, between January 2016 and June 2017, with displaced intra-articular femoral fractures, were prospectively recruited. All patients underwent cemented modular bipolar hip hemiarthroplasty (Profemur Z, MicroPort Orthopedics Inc., Arlington, TN, USA) via the Hardinge approach, with the patient positioned in lateral decubitus. The surgical procedures were performed by the same surgical and anesthesiology team, under spinal anaesthesia. All patients underwent clinical and radiographic follow-up up to 24 months. Complications and re-operations were recorded. Clinical evaluation was performed using the Harris Hip Score (HHS), Osteoporosis Quality of Life Questionnaire QUALEFFO-41 and EuroQol-5D (EQ-5D) questionnaire. Anteroposterior pelvis x-rays were performed preoperatively, postoperatively and at 1, 3, 6, 12 and 24 months follow-up. Results: 118 patients met the inclusion criteria (male: 50; female: 68; mean age: 74.3 years; range 65–88 years) and were included in the current study. 67 patients out of 118 (56.8%) were managed by senior orthopaedic surgeons (Group A), whereas the remaining 51 patients out of 118 (43.2%) were treated by orthopaedic residents (Group B). Hip hemiarthroplasties performed by senior surgeons showed the prevalent use of straight (short or long) necks, whereas, in surgical procedures performed by residents, there was a significantly higher use of varus/valgus, anteverted or retroverted necks. The overall complication rate was significantly higher in Group-B patients, compared with Group-A patients ( p = 0.002). The length of hospital stay and the mean clinical scores at 24 months follow-up showed no significant differences. Conclusions: Hip hemiarthroplasty with modular neck can be safely employed during the learning curve of orthopaedic residents. Great efforts, however, should be made in future to improve residents' training in the management of FNFs.